2009
DOI: 10.2174/092986709788682065
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Virucidal Activities of Natural Products

Abstract: Virus infection is one of the major threats to human health and can be avoided by minimizing exposure to infectious viruses. Viral clearance of pharmaceutical products and sanitization of skin and mucosal surfaces would reduce such exposures. Even with such care, virus infection does occur, requiring effective treatments by antiviral or virucidal agents. Natural products, in particular ingredients of foods and drinks we normally consume or metabolites present in human body at low concentrations, would have adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Considering the potential safety of natural dietary products, in previous studies, we examined the antiviral and virucidal activities of various natural products and their components (1-3, reviewed in ref. 4). We found that caffeic acid inhibits the multiplication of herpes simplex virus type 1 (HSV-1) in vitro by interfering mainly with the early stages of HSV-1 multiplication in the infected cells prior to the completion of viral genome DNA replication, independently of its cytotoxic action (5).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the potential safety of natural dietary products, in previous studies, we examined the antiviral and virucidal activities of various natural products and their components (1-3, reviewed in ref. 4). We found that caffeic acid inhibits the multiplication of herpes simplex virus type 1 (HSV-1) in vitro by interfering mainly with the early stages of HSV-1 multiplication in the infected cells prior to the completion of viral genome DNA replication, independently of its cytotoxic action (5).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, much attention has been focused on dietary factors that reduce the risk of cancers [2]. Natural products or phytonutrients appear to be potent therapeutics for viral diseases and cancers [3-5]. …”
Section: Introductionmentioning
confidence: 99%
“…The research and development of new natural compounds with antiviral activity have attracted the researchers' interest [17, 18] as good candidates suitable for further modification and optimization of bioactivity.…”
Section: Discussionmentioning
confidence: 99%